The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1063/1.444239
|View full text |Cite
|
Sign up to set email alerts
|

A bi n i t i o MO studies of electronic states and Mössbauer spectra of high-, intermediate-, and low-spin Fe(II)-porphyrin complexes

Abstract: A b initio LCAO SCF MO calculations were carried out on Fe-porphine, Fe-porphine-pyridine, and Fe-porphine-pyridine-carbonmonoxide which are typical intermediate-, high-, and low-spin complexes, respectively. Mössbauer spectra of ferrous porphyrins were analyzed theoretically by the evaluation of isomer shift (IS), quadrupole splitting (QS), sign and direction of the principal component of electric field gradient tensor, and asymmetry parameter for the complexes. The calculated values have a good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 46 publications
6
39
1
Order By: Relevance
“…All energy differences are reported with reference to the lowest 'E, state. These differences agree with those obtained by Obara and Kashiwagi [4], although basis sets and geometry differ. Also, our basis gives a 'E, reference energy that is 1.8 hartree lower than the energy reported by Kashiwagi for a slightly larger basis set.…”
Section: Scf Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…All energy differences are reported with reference to the lowest 'E, state. These differences agree with those obtained by Obara and Kashiwagi [4], although basis sets and geometry differ. Also, our basis gives a 'E, reference energy that is 1.8 hartree lower than the energy reported by Kashiwagi for a slightly larger basis set.…”
Section: Scf Resultssupporting
confidence: 91%
“…Obara and Kashiwagi [4] conjectured that the lowest 3E, SCF state would configurationally mix with the second SCF 3E, state (see Table I for d configurations). They suggested that such mixing would correct the predicted quadrupole splittings to repro-duce the experimental quadrupole splitting for Fe"(TPP).…”
Section: Resultsmentioning
confidence: 98%
“…In large basis set CAS-PT2 calculations with 14 electrons in 13 active orbitals, the quintet state was found lower than the triplet by 19.6 kcal/mol [43]. At the B3LYP level the triplet is actually favored by 6.9 kcal/mol [44], in agreement with experiments for very similar systems [45,46,47,48]. The similarity between Fe(II)-porphine and the experimentally studied systems has been convincingly demonstrated by recent calculations [49].…”
Section: Resultssupporting
confidence: 70%
“…This supports also agreement of Fe−N distances calculated in our study with the X‐ray spectroscopy (see Figure a). Guiding by predictions of the experimentally obtained ground state multiplicity, all computational studies on the character of the FePc electronic structure performed with single‐ and multi‐reference methods assumed the triplet only without consideration of other possible multiplicities.…”
Section: Figurementioning
confidence: 99%